2022
DOI: 10.3390/ijms23052764
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds for Counteracting Nonalcoholic Fatty Liver Disease (NAFLD): Advantages and Limitations of the Suggested Candidates

Abstract: The booming prevalence of nonalcoholic fatty liver disease (NAFLD) in adults and children will threaten the health system in the upcoming years. The “multiple hit” hypothesis is the currently accepted explanation of the complex etiology and pathophysiology of the disease. Some of the critical pathological events associated with the development of NAFLD are insulin resistance, steatosis, oxidative stress, inflammation, and fibrosis. Hence, attenuating these events may help prevent or delay the progression of NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 124 publications
(172 reference statements)
0
19
0
Order By: Relevance
“…For safety, silymarin was found to be safe and well tolerated (68). The current study found that silymarin has antiinflammatory, immunomodulatory, antifibrotic, antioxidant, and liver regeneration properties in the treatment of NAFLD (152,153). This meta-analysis and systematic review showed that silymarin was effective in improving ALT and AST and reducing hepatic fat accumulation and liver stiffness in NAFLD patients.…”
Section: Silymarinmentioning
confidence: 59%
“…For safety, silymarin was found to be safe and well tolerated (68). The current study found that silymarin has antiinflammatory, immunomodulatory, antifibrotic, antioxidant, and liver regeneration properties in the treatment of NAFLD (152,153). This meta-analysis and systematic review showed that silymarin was effective in improving ALT and AST and reducing hepatic fat accumulation and liver stiffness in NAFLD patients.…”
Section: Silymarinmentioning
confidence: 59%
“…Lifestyle interventions, like dietary changes and exercise, should be combined with the administration of so-called bio-active natural compounds, such as polyphenols, polyunsaturated fatty acids, vitamin E, quercetin, phytosterols, fructo-oligosaccharides, and carbohydrate-dietary fibers [ 2 , 22 ]. Numerous clinical studies confirmed the ability of some of this natural product metabolites to exert beneficial effect(s) in the cellular mechanisms involved in the onset and progression of NAFLD [ 20 , 23 ]. Moreover, several studies published in the literature in recent years have confirmed the beneficial effects of phytosterols (PSs) on lipid metabolism, as serum cholesterol-lowering, and the evolution of NAFLD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some natural compounds such as coffee (and its components), tormentic acid, verbascoside, and silymarin showed protective effects in ameliorating the critical pathological events involved in NAFLD. For example, silymarin has been widely used in the treatment of various liver disorders because of its hepatoprotective properties, including anti-inflammatory, antiproliferative, immunomodulatory, and nticholesterolemic properties ( Salvoza et al, 2022 ). Baicalein, a bioactive flavone, is isolated from Scutellariae baicalensis , which is a traditional Chinese herb.…”
Section: Introductionmentioning
confidence: 99%